Nuchal gland system: a novel defensive mechanism evolved in Asian natricine snakes - Mori, A.; Jono, T.; Takeuchi, H.; Yoshida, T.; Ding, L.; De Silva, A.; Tsai, T.S.; Nguyen, T.T.; Mahaulpatha, W.A.D.; Das, I.; Zhu, G.; Tang, Y.; et al. (My University, 2016)
Attached

Because o f their carnivorous habit, snakes are often considered top predators in animal community. However, snakes are also exploited by m any other predatory animals, and therefore, have evolved a variety o f antipredator mechanisms. Nuchal glands are unique organs first described in a Japanese natricine snake, Rhabdophis tigrinus in 1935. Nuchal glands, which are ontogenetically mesodermal origin, consist o f a series o f paired organs embedded under the skin o f the neck region. These glands contain bufadienolides, a group o f cardiotonic steroids, w hich are sequestered from the skin toxins o f toads consumed as prey. To use these toxic chemicals effectively to deter predation, R. tigrinus performs peculiar antipredator displays, such as neck arch and neck butting. Several other natricine species belonging to Rhabdophis, Macropisthodon, and Balanophis have similar organs, which are collectively called as nucho-dorsal glands. Some o f these species have glands not only in the neck but also in the entire length o f the body. W e provide a brief overview o f the history o f the studies on the nuchal glands and related behavioral, ecological, and physiological features. W e then present updated knowledge o f the nuchal glands, especially concerning their morphological variation. Finally, w e discuss the diversity o f this unique defensive system, which involves correlated traits among morphological, ecological, behavioral, and physiological features.
Keywords: Rhabdophis; nuchal glands; antipredator mechanism; Asian natricines